URGENSI LEMBAGA AMIL ZAKAT & PERKEMBANGANNYA DI ACEH - fasya, fasya (Al - Muamalat, 2016)
Their income gap in Aceh as a result of the unequal distribution of income in society, as well as government policies that have not touched the middle to lower (poor) zakat is one of the pillars of Islam and at the time of the Prophet zakat is one means to reduce poverty, in terms of the Baitul Mal Aceh is an institution in charge of collecting alms from the people who are able and distribute it to the poor. As this study aims to determine the History of Institutions Zakat Management in Aceh and urgency, Since 1973, Aceh has formed an agency called Agency for Control of Assets of Religious (BPHA-) by Decree (SK) Governor No. 52 of 1973, in 1976 the institution this changed with the name of religion Harta Agency (BHA) Governor's Decree No. 407 of 1976, in 1995 the institute changed its name to Manajer alms and Sadaqah Infaq (BAZIS) then the last change is the release of Decree No. 18/2003 Date l6 July 2003 on the Establishment of Organization of Work and Organizational Structure Baitul Mal Nanggroe Aceh Darussalam, the institution was renamed the Agency BAZIS Baitul Mal and just started ratified on January 13, 2004. Ugensi amil zakat institutions, among others: 1) to ensure security and discipline the tax payers (muzakki), 2) to keep the feeling of inferiority the mustahiq zakat when faced directly to receive alms from muzakki, 3) to achieve efficiency and effectiveness, as well as the right targets in the use of zakat according to the priorities that exist in a place, 4) to show the greatness of Islam in the spirit of Islamic governance, 5) Improving the effectiveness and efficiency of service delivery in the management of zakat; and 6) Increase the benefits of charity for the public welfare and poverty reduction.